In Vitro Callus Induction and Growth of Stevia (Stevia rebaudiana Bertoni M.) with Difference Concentrations of PEG (Polyethylene Glycol) and Light Conditions - Mohamad Ana Syabana; Pipit Marianingsih; Nuniek Hermita; Iim Rohimah (Universitas Sultan Ageng Tirtayasa, 2017)
Stevia (Stevia rebaudiana Bert. M.) is known as a natural non-caloric sweetener. This plants contain glycoside such steviosida type, mainly on the leave contain sweetness level between 200-300 cane sugar but the calorie is very low. This research was aimed to determine difference effects of PEG (Polyethylene Glycol) concentrations and the light conditions on Stevia (Stevia rebaudiana Bert. M.) callus induction in vitro. This research was conducted from April to June 2016 at Biotechnology Laboratory Faculty of Agriculture, Sultan Ageng Tirtayasa University. This research used a completely randomized design (CRD), which consisted of two factors with three replications. Concentrations of PEG as first factor consisted of four levels (0 mg/L, 5 mg/L, 15 mg/L, and 25 mg/L). Light conditions as second factor consisted of two levels (Dark and Light). The results showed that the concentrations of PEG (Polyethylene Glycol) did not significantly effect the time of callus appearance and diameter of callus on 4, 5 and 6 weeks after planting. Dark condition was the best conditions for callus induction of stevia. The texture of callus was compact on all treatments and the callus dominant color produced is golden brown.